DCE‐MRI of the human kidney using BLADE: a feasibility study in healthy volunteers - Lietzmann, Florian; Zöllner, Frank G.; Attenberger, Ulrike; Haneder, Stefan; Michaely, Henrik J. M.; Schad, Lothar R. (Journal of magnetic resonance imaging, 2012)
Purpose: To evaluate the degree of motion compensation in the kidney using two different sampling methods, each in their optimized settings: A BLADE k‐space acquisition technique and a routinely used kidney perfusion acquisition scheme (TurboFLASH). Materials and Methods: Dynamic contrast enhanced magnetic resonance examinations were performed in 16 healthy volunteers on a 3 Tesla MR‐system with two parameterizations of the BLADE sequence and the standard reference acquisition scheme. Signal intensity enhanced time curves were analyzed with a mathematical model and a widely published separable compartment model on cortex regions to assess robustness versus motion artifacts. Results: BLADE‐measurements with a strip‐width of 32 lines constituted the smallest mean values for the sum of squared errors (6065 ± 4996) compared with the measurement with a strip‐width of 64 lines (13849 ± 14079) or the standard TurboFLASH (11884 ± 8076). Calculations concerning goodness of the fit of the applied compartment model yielded an overall average of the Akaike Fit Error of 732 ± 141 for BLADE (646 ± 149 for a strip‐width of 32 lines, 816 ± 53 for 64 lines) and 1626 ± 303 for the TurboFLASH (TFL) sequence. Conclusion: We demonstrated that renal dynamic contrast enhanced magnetic resonance imaging using BLADE k‐space sampling with a strip‐width of 32 is significantly less sensitive to motion than a widely published Turbo‐Flash sequence with nearly similar parameters.
First published: 29 November 2011
Gesehen am 10.11.2019